PENGARUH PENAMBAHAN PUPUK MAJEMUK NPK TERHADAP PERTUMBUHAN DAN KADAR PROTEIN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) SEBAGAI PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI KONSEP JAMUR (FUNGI) DI KELAS X SMA - Mahadi, Imam; Suryawati, Evi; ', Nurkameria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research was conducted to determine the effect of NPK complex fertilizers to the growth and protein content white oyster mushrooms (pleurotus ostreatus) on March-May 2016. The results used as module development of biology learning of concept mushrooms (fungi) in class x senior high school. The study consisted of two phases, the first effect of NPK complex fertilizers to the growth and protein content white oyster mushrooms (pleurotus ostreatus) using non factorial completely randomized design that consist 5 treatments and 3 replicatesand totally obtain 15 experimental design. It would further DMRT test if effect. The observed parameters include growth and protein content white oyster mushrooms. The second phase, developing a module with concept of mushrooms (fungi) by using ADDIE models. Based on the survey results revealed that the addition of NPK effect on all parameters observed where the best dosage with the addition of NPK 10gr / 1 kg of growing media. The results of the research used to development of modules and get valid with a mean value of 4.03.Keywords: NPK complex fertilizer, growth, protein content, white oyster mushrooms, module